EXPERIENCE OF EXTRACORPOREAL SHOCKWAVE LITHOTRIPSY FOR KIDNEY AND UPPER URETERIC STONES BY ELECTROMAGNETIC LITHOTRIPTOR - Wazir, Bakhtawar Gul; Haq, Mian Iftikhar ul; Haq, Faheem ul; Nawaz, Akhtar; Nawaz, Ahmed; ullah, Ikram; Jamil, Mohammad (Journal of Ayub Medical College Abbottabad, 2010)
Background: Extracorporeal Shock Wave Lithotripsy (ESWL) is a non-invasive treatment of urinary stones which breaks them, by using externally applied, focused, high intensity acoustic pulse, into smaller pieces so that they can pass easily through ureter. Shock wave generation, focusing, coupling and stone localisation by fluoroscope or ultrasound are the basic components of ESWL. ESWL has some complications and is contraindicated in certain situations. The aim of this study was to evaluate the effectiveness and safety of ESWL in kidney and upper ureteric stones by Electromagnetic Lithotriptor. Methods: All adult patients with renal and upper ureteric stones having a diameter of up to 1 Cm were included in the study. Basic evaluation such as history, examination, ultrasound and excretory urography were performed. Electromagnetic lithotripsy was done and data were collected on a printed proforma from 1st January 2008 to 30th March 2009 in Institute of Kidney Diseases, Peshawar. Results: Out of a total of 625 patients 463 were male and 162 were female; 67.36% of patients were having renal stones, 23.84% upper ureteric and 8.8% both renal and ureteric stones. Complications noted were renal colic in 9.76%, haematuria in 3.2%, steinstrasse in 2.72%, and fever in 1.12% of patients. The stone free rate was 89% and 7% of patients were having stone fragments <4 mm. ESWL failed in 4% of patients. Conclusion: ESWL is a safe and effective way of treating kidney and upper ureteric stones. Keywords: Extracorporeal shock wave lithotripsy (ESWL), kidney and upper ureteric stones